Implementasi Peraturan Bupati Gresik No. 34 Tahun 2017 Tentang Dana Desa - Nande, Valeria Deo (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2021)
The reality of using village funds in 2018 has been used well and has fulfilled the expectations and needs of the community. It can be seen that the policy implementers have the ability to manage the existing budget, where the implementers of the policy work in a synergy, transparent and in accordance with the regulation of Regent Gresik number 34 of 2017 on village funds, village funds in 2018 in the Kepatihan village are prioritized for development alone this is because when a village meeting (musrenbang) is held, it is seen from the proposal that there is a lot of development that must be built. This is evidenced by the development of the Kepatihan village, so that it can be said that the use of village funds has been optimal and should be appreciated by the community where they feel that the development has been evenly distributed. The findings of this study indicate that "The implementation of village funds is in accordance with existing regulations and can be said to be successful. In Article 4 paragraph 1 in the regulation of Regent Gresik number 34 of 2017 said that Village income should be publicized to the general public that can be accessed by village communities , and this has been done by policy implementers, thus the community knows the details of village funds and the amount of village funds received in 2018.